Human Computer Interaction (HCI) : A Narrative Review (Architecture Image Studies, 2026)
The rapid evolution of computer technology has brought the field of human-computer interaction (HCI) into sharper focus, especially among younger, technically adept user populations. In this review paper, we explore the concept of the mental model within HCI: how users form internal representations of interactive systems, and how those representations influence usability, engagement, and learning. The study is structured in two complementary ways. First, we examine contemporary approaches, current outcomes, and emerging trends in HCI - identifying how mental models are evolving in response to new interaction paradigms, emotional intelligence considerations, and high-fidelity prototyping techniques. Second, we trace earlier foundational research - highlighting promising lines of inquiry that have, to some extent, lagged behind or not fully matured, and considering why they remain relevant today. A particular emphasis of this paper is the role of user emotional intelligence - how a user’s emotional and cognitive state can align more closely with system behaviors to create more “user-like” interaction and fidelity in prototyping, which underpins how closely the interactive system approximates real-world usage. Ultimately, the design and development of automated systems capable of such sophisticated, emotionally aware and mentally congruent interaction remain in progress. By reviewing both the state-of-the-art and the under-explored pathways, this paper offers a holistic perspective on mental models in HCI, helping to define future research directions and design imperatives.